2019
DOI: 10.1093/ajcp/aqz100
|View full text |Cite
|
Sign up to set email alerts
|

Improving Outcomes

Abstract: Objectives To determine the strength of study design and outcomes in literature describing pathology education for medical students. Methods A search was conducted for articles related to pathology education published over 45 years describing an educational intervention. The primary data collected included phase of education, domain of objectives, number of learners and institutions, type of intervention, use of a comparison/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Most educational intervention studies in pathology have been described as having poor experimental design, including fewer than 100 study participants, lacking data collection among multiple institutions, and failing to provide statistical significance. 23 No medical education intervention studies in a recent review article examined outcomes at a distance from the intervention. 23 The need for an evidence base in the practice of medical education is essential 24 and our study establishes an evidence base for the MPATH-Dx schema, including a large nationwide sample of pathologists from multiple institutions and establishing long-term outcomes of the intervention with statistical significance and confidence intervals provided.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most educational intervention studies in pathology have been described as having poor experimental design, including fewer than 100 study participants, lacking data collection among multiple institutions, and failing to provide statistical significance. 23 No medical education intervention studies in a recent review article examined outcomes at a distance from the intervention. 23 The need for an evidence base in the practice of medical education is essential 24 and our study establishes an evidence base for the MPATH-Dx schema, including a large nationwide sample of pathologists from multiple institutions and establishing long-term outcomes of the intervention with statistical significance and confidence intervals provided.…”
Section: Discussionmentioning
confidence: 99%
“… 23 No medical education intervention studies in a recent review article examined outcomes at a distance from the intervention. 23 The need for an evidence base in the practice of medical education is essential 24 and our study establishes an evidence base for the MPATH-Dx schema, including a large nationwide sample of pathologists from multiple institutions and establishing long-term outcomes of the intervention with statistical significance and confidence intervals provided. Other study strengths include a high response rate (71%) among invited dermatopathologists, which surpasses standards for physician surveys.…”
Section: Discussionmentioning
confidence: 99%
“…Animations [ 6 ], interactive online quizzes [ 3 ], adaptive e-learning [ 7 ], and virtual reality tours [ 8 ] are some of the innovative strategies that have been explored. Importantly, careful curricular planning, with instructional designs grounded in educational theory, and use of comparable comparisons when appropriate are vital for the successful evaluation of new learning activities [ 1 , 9 11 ]; unfortunately, many educational innovations described in the literature do not meet these standards [ 2 , 6 , 12 ]. For example, in their review of animations used for medical education, Yue et al found that very few followed the principles of the cognitive theory of multimedia learning [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, in their review of animations used for medical education, Yue et al found that very few followed the principles of the cognitive theory of multimedia learning [ 6 ]. Additionally, McBrien et al found that fewer than half of the Pathology educational interventions they reviewed described the use of a control group [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25][26][27][28] However, there is a lack of robust guidelines and experimental approaches in the evaluation and critical appraisal of these educational interventions. 29,30 To that end, we sought to systematically characterize, evaluate, and compare the various types of assessment questions employed within an introductory course in general pathology during the first year of medical school instruction at our institution. Our goal was to use item-level analysis in order to identify specific assessment characteristics that might influence and predict student performance in this setting and to provide data that could be used to guide future evidence-based decision-making in promoting higher-level learning approaches.…”
mentioning
confidence: 99%